DNA analysis of low‐ and high‐density fractions defines heterogeneous subpopulations of small extracellular vesicles based on their DNA cargo and topology. Issue 1 (27th August 2019) - Lázaro‐Ibáñez, Elisa; Lässer, Cecilia; Shelke, Ganesh Vilas; Crescitelli, Rossella; Jang, Su Chul; Cvjetkovic, Aleksander; García‐Rodríguez, Anaís; Lötvall, Jan
ABSTRACT: Extracellular vesicles have the capacity to transfer lipids, proteins, and nucleic acids between cells, thereby influencing the recipient cell's phenotype. While the role of RNAs in EVs has been extensively studied, the function of DNA remains elusive. Here, we distinguished novel heterogeneous subpopulations of small extracellular vesicles (sEVs) based on their DNA content and topology. Low‐ and high‐density sEV subsets from a human mast cell line (HMC‐1) and an erythroleukemic cell line (TF‐1) were separated using high‐resolution iodixanol density gradients to discriminate the nature of the DNA cargo of the sEVs. Paired comparisons of the sEV‐associated DNA and RNA molecules showed that RNA was more abundant than DNA and that most of the DNA was present in the high‐density fractions, demonstrating that sEV subpopulations have different DNA content. DNA was predominately localised on the outside or surface of sEVs, with only a small portion being protected from enzymatic degradation. Whole‐genome sequencing identified DNA fragments spanning all chromosomes and mitochondrial DNA when sEVs were analysed in bulk. Our work contributes to the understanding of how DNA is associated with sEVs and thus provides direction for distinguishing subtypes of EVs based on their DNA cargo and topology.